New Glycosides from the Fruits of Nicandra physaloides - Yan Liu; Hai-Bing Jiang; Zhen-Peng Xu; Yan-Gang Cheng; Shao-Wa Lv; Bing-You Yang; Hong-Wei Guo; Hai-Xue Kuang (Molecules, 2017)
Three new glycosides (1–3) and 15 known ones (4–18) were isolated and identified from the fruits of Nicandra physaloides. The structures of these compounds were established by 1D and 2D NMR spectra and HR-ESI-MS. The compounds (4–18) were the first time isolated from the Nicandra genus and they (except 8, 10, 14) exhibited inhibitions on the NO release of LPS-induced RAW 264.7 cells with IC50 values from 26.9 to 47.5 μM.